2015
DOI: 10.1158/1940-6207.capr-15-0004
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Efforts to Reduce Cervical Cancer through State-Level Comprehensive Cancer Control Planning

Abstract: Reducing cervical cancer disparities in the United States requires intentional focus on structural barriers such as systems and policy that impact access to human papillomavirus (HPV) vaccination, cervical cancer screening, and treatment. Such changes are difficult and often politicized. State comprehensive cancer control (CCC) plans are vehicles that, if designed well, can help build collective focus on structural changes. Study objectives were to identify the prioritization of cervical cancer in state CCC pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…[35][36][37][38] Another emerging issue which has been explored elsewhere is the tendency to focus on females for HPV related policy and interventions. [38][39][40][41] Virginia's language of limiting its…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38] Another emerging issue which has been explored elsewhere is the tendency to focus on females for HPV related policy and interventions. [38][39][40][41] Virginia's language of limiting its…”
Section: Discussionmentioning
confidence: 99%
“…school-entry requirements to only female students does not reflect CDC guidelines 41 and shifts the burden of cervical cancer prevention entirely to female students. As we note elsewhere, 40 this is likely reflective of the changing science around HPV and the delay in reflecting such science in policy, as Virginia enacted this law in 2007, 9 the same year that CDC's Advisory Community on Immunization Practices (ACIP) issued its first recommendations related to HPV vaccination. 42 These recommendations exclusively applied to females.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based early detection or screening is currently recommended by USPSTF for only a few types of cancer: mammography for breast cancer, pap smear for cervical cancer, colonoscopy (and other tests) for colorectal cancer, and the use of low-dose computed tomography for lung cancer screening [22]. Cancer plan reviews have shown that the vast majority contain cervical cancer content with 80.4% containing educational activities with a focus on individual behavior change [48]. Clinician behavior change was included in 41.2% of plans, and 11.7% identifying specific systems or environmental changes to bring about this change in clinicians [48].…”
Section: Promoting Early Detection Of Cancermentioning
confidence: 99%
“…Cancer plan reviews have shown that the vast majority contain cervical cancer content with 80.4% containing educational activities with a focus on individual behavior change [48]. Clinician behavior change was included in 41.2% of plans, and 11.7% identifying specific systems or environmental changes to bring about this change in clinicians [48]. This work does extend to NCCCP-funded areas of relatively low resources, such as the USAPIJs.…”
Section: Promoting Early Detection Of Cancermentioning
confidence: 99%
“…The interventions include prevention, early detection (screening and diagnosis) and treatment (20). Improvements in CC screening, involve addressing systems challenges and changing policies of public health structural interventions which alter structural context for health and are often politicised (21). Women are more likely to seek help when the disease is already at advanced stages (22).…”
mentioning
confidence: 99%